Digital Government in the State of Tabasco: An Exploratory Analysis - Córdova Pérez, Rafael Jesús; Magaña Rodríguez, Martín Ernesto; Morales Cárdenas, Tomás Francisco (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2024)
OBJECTIVE: To identify how the government of the state of Tabasco has implemented digital government as part of its legislation and administrative processes. MATERIAL AND METHOD: It is determined under a qualitative approach, through documentary research, with a hermeneutic perspective, where literary review of documents, indicators and consultation of public government websites at the national and state level are considered. RESULTS: Digital government is a vital component for the modernization of public administration, offering multiple benefits in terms of efficiency, transparency and citizen participation. According to the information collected in the national context, the state of Tabasco is located below the average in the State Digital Governance Index, even though the catalog of services that can be performed through digital portals is extensive. CONCLUSIONS: Digital Government improves the efficiency of public administration by digitizing processes and using technologies; however, although Tabasco has implemented laws and policies to advance digital government, it still faces significant challenges, which must be resolved to align with the new trends given in the international and national context.